Battery
By adopting a double-layer coating structure in the negative electrode sheet of the battery, using the combination of silicon-carbon material and second graphite, and combining the regulation of the ceramic separator, the fracture problem caused by the expansion of the negative electrode sheet during the charging and discharging process is solved, and a higher energy density and cycling stability are achieved.
Patent Information
- Application Number
- CN202411996187.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
When existing batteries use negative electrode silicon doped material during charging and discharging, they are prone to severe expansion, resulting in fracture of the electrode pieces and causing battery failure.
Using a negative electrode sheet with a double-layer coating structure, silicon carbon material is added to the first coating to achieve shallow filling and light discharge, second graphite is used in the second coating, and the average particle size of the graphite and the thickness of the ceramic layer are coordinated through a ceramic diaphragm to meet a specific particle size ratio and thickness range to limit the extension of the electrode sheet coating.
Effectively alleviate the expansion of the negative electrode sheet, reduce the risk of electrode sheet fracture, improve the energy density and cycle stability of the battery, reduce the expansion rate of the battery, and avoid battery failure caused by electrode sheet fracture.
Smart Images

Figure CN119812435A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical devices, and in particular to a battery. Background Art
[0002] Batteries are common electrochemical devices with a wide range of applications. The energy density of a battery (i.e., the amount of energy that can be stored per unit volume or unit mass) is a key performance indicator. In the prior art, solutions to improve the energy density of a battery include using negative electrode silicon-doped materials in the negative electrode sheet, which can effectively improve the energy density of the battery. However, during the battery charging and discharging process, silicon-doped negative electrode sheets using negative electrode silicon-doped materials are prone to severe expansion, causing the negative electrode sheet to expand significantly, which can easily cause the negative electrode sheet to break and cause battery failure. Therefore, how to avoid electrode sheet breakage and reduce the battery expansion rate while increasing the battery energy density (capacity) is a technical problem that needs to be urgently solved in this field. Summary of the invention
[0003] The present invention provides a battery, which can alleviate the expansion of the negative electrode sheet, reduce the risk of the electrode sheet breaking, and take into account both reducing the battery expansion rate and increasing the battery capacity, effectively overcoming the defects of the prior art.
[0004] The present invention provides a battery, comprising: a negative electrode sheet, comprising a negative electrode current collector, and a negative electrode active layer located on at least one side of the negative electrode current collector, the negative electrode active layer comprising a second coating layer, and a first coating layer located between the negative electrode current collector and the second coating layer, the first coating layer comprising a first active material, the first active material comprising a silicon-carbon material, the second coating layer comprising a second active material, the second active material comprising a second graphite; a diaphragm, comprising a base film, and a ceramic layer located on at least one side of the base film, the ceramic layer comprising a ceramic material; an average particle size D3 of the second graphite in the second coating layer, an average particle size D4 of the ceramic material 31 Satisfies: 3≤D3 / D 31 ≤350, the thickness of the ceramic layer H 31 Satisfy 0.5μm≤H 31 ≤6μm.
[0005] According to one embodiment of the present invention, 4≤D3 / D 31 ≤70; and / or, 5μm≤D3≤22μm; and / or, 50nm≤D 31≤2μm; and / or, the first active material also includes a first graphite; preferably, an average particle size D2 of the first graphite in the first coating layer is greater than an average particle size D3 of the second graphite in the second coating layer, preferably 0.3≤D3 / D2≤1; preferably, the maximum particle size D1 of the silicon-carbon material in the first coating layer and the average particle size D2 of the first graphite in the first coating layer satisfy 0.5≤D1 / D2≤1.5; preferably, 5μm≤D1≤20μm.
[0006] According to one embodiment of the present invention, the battery further comprises an electrolyte, and the electrolyte comprises a sulfonate; preferably, the mass percentage content e of the sulfonate in the electrolyte and the tensile strength S1 of the negative electrode current collector satisfy S1 / e≥550, preferably 550≤S1 / e≤60000, and the unit of S1 is MPa; preferably, the tensile strength S1 of the negative electrode current collector is ≥400MPa; preferably, the mass percentage content e of the sulfonate in the electrolyte is 0.1% to 20%; preferably, the sulfonate comprises 1,3-propane sultone and / or 1,3-propylene sultone.
[0007] According to one embodiment of the present invention, the thickness H of the negative electrode current collector is 10 , the tensile strength S1 of the negative electrode current collector, the mass ratio X of the silicon-carbon material to the graphite in the negative electrode active layer satisfies H 10 ×S1 / X≥1600, preferably 1600≤(H 10 ×S1) / X≤660000, S1 is in MPa, H 10 The unit is μm; preferably, 3μm≤H 10 ≤12μm; preferably 1%≤X≤50%.
[0008] According to one embodiment of the present invention, the ceramic layer is located on the surface of the base film facing the negative electrode sheet; and / or the battery also includes a positive electrode sheet, and the diaphragm is located between the positive electrode sheet and the negative electrode sheet; the bonding force between the diaphragm and the positive electrode sheet is greater than the bonding force between the diaphragm and the negative electrode sheet.
[0009] According to one embodiment of the present invention, the battery further comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material, the positive electrode active material contains yttrium element; preferably, the first coating further comprises graphite, 400≤y / X≤200000, y is the yttrium content in the positive electrode active layer, the unit of y is ppm, and X is the mass ratio of the silicon-carbon material to the graphite in the negative electrode active layer; preferably, 100ppm≤y≤2000ppm.
[0010] According to one embodiment of the present invention, the battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side surface of the positive electrode current collector; 20 ×S2 / X≥600, preferably 600≤(H 20 ×S2) / X≤300000,H 20 is the thickness of the positive electrode current collector, in μm, S2 is the tensile strength of the positive electrode current collector, in MPa, and X is the mass ratio of the silicon-carbon material to the graphite in the negative electrode active layer; preferably, 5 μm ≤ H 20 ≤20μm; preferably, 50Mpa≤S2≤300Mpa.
[0011] According to one embodiment of the present invention, the first coating layer also includes a first graphite; and / or, the mass ratio X of the silicon carbon to the graphite in the negative electrode active layer and the mass percentage a of the silicon element in the silicon-carbon material satisfy 0.35%≤a×X≤35%; and / or, the mass percentage a of the silicon element in the silicon-carbon material is 35% to 70%; and / or, the silicon element content in the silicon-carbon material tends to decrease from the center of the silicon-carbon particles to the edge of the silicon-carbon particles; and / or, the mass ratio of the silicon carbon to the graphite in the negative electrode active layer is 1% to 50%, preferably 4% to 30%.
[0012] According to one embodiment of the present invention, the surface of the second coating layer is provided with recesses; preferably, the width of the recesses is 50 μm to 160 μm; preferably, the depth of the recesses is 3 μm to 40 μm; preferably, the spacing between the recesses is 0.3 to 3 mm.
[0013] According to one embodiment of the present invention, the negative electrode sheet includes a negative electrode tab; the negative electrode active layer includes a main body area, a first recessed area, and a second recessed area located between the main body area and the first recessed area, and the negative electrode tab is arranged in the first recessed area; the battery also includes a tab tape, the tab tape includes a first connecting portion located on the side of the negative electrode tab away from the negative electrode current collector, and a second connecting portion located on the side of the first recessed area away from the negative electrode current collector, and a side surface of the second connecting portion away from the negative electrode current collector does not exceed a side surface of the main body area away from the negative electrode current collector.
[0014] The battery provided by the present invention adds silicon-carbon material to the first coating layer close to the negative electrode current collector (that is, the lower layer close to the negative electrode current collector in the double coating layer of the negative electrode sheet), and reduces the side reaction on the surface of the silicon-carbon particles and the expansion of the silicon-carbon particles by virtue of the shallow charge and discharge effect of the silicon particles, thereby improving the energy density and relieving the large extension (or expansion) of the negative electrode sheet (silicon-doped negative electrode) caused by the expansion of the silicon-carbon particles, thereby improving the problem of the electrode sheet fracture; at the same time, a ceramic diaphragm is used, and the average particle size D3 of the graphite in the second coating layer and the thickness H of the ceramic layer are coordinated and regulated. 31 , the average particle size D of ceramic materials 31 , so that it satisfies 3≤D3 / D 31 ≤350、0.5μm≤H 31 ≤6μm. Under such a battery composition and structural system, the diaphragm can help restrain the extension of the positive electrode coating (paste), reduce the risk of pole piece breakage, and improve the battery's energy density (capacity) and cycle stability. It also reduces the battery expansion rate and avoids problems such as battery failure caused by pole piece breakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of the projection structure of the first coating on the first current collector according to one embodiment of the present invention;
[0016] Figure 2 This is a schematic diagram of the projection structure of the first coating on the first current collector according to another embodiment of the present invention;
[0017] Figure 3 is a schematic diagram of the cross-sectional structure of a first pole piece according to an embodiment of the present invention;
[0018] Figure 4 Electron microscope image of silicon carbon material used in some embodiments in backscattered electron mode (BSE mode);
[0019] Figure 5 It is a schematic diagram of the structure of a negative electrode sheet with a tab tape provided on the surface of the negative electrode tab in one embodiment of the present invention;
[0020] Figure 6 Schematic diagram of the stacked structure of the negative electrode sheet, the separator and the positive electrode sheet according to an embodiment of the present invention.
[0021] Explanation of reference numerals: 1; negative electrode sheet; 11: negative electrode current collector; 12: negative electrode active coating; 121: first coating; 122: second coating; 123: first recessed area; 124: second recessed area; 125: third recessed area; 126: fourth recessed area; 127: main area; 101: first side; 102: second side; 13: recess; 130: recess group; 14: negative electrode tab; 2: tab adhesive tape; 21: first connecting portion; 22: second connecting portion; 3; diaphragm; 31: ceramic layer; 32: base film; 4: positive electrode sheet; 41: positive electrode current collector; 42 : Positive electrode active layer; W1: width of the first recessed area, width of the third recessed area; W2: width of the tab tape; W3: width of the slot; L: width of the recess; △L: spacing between two adjacent recesses; h: depth of the recess; △L1: distance between the outer edge of the recess closest to the first side of the second coating and the outer edge of the first side of the second coating; △L2: distance between the outer edge of the recess closest to the second side of the second coating and the outer edge of the second side of the second coating; w: distance between the recesses in two adjacent recess groups in the second direction c; b: first direction; c: second direction; d: third direction. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0023] An embodiment of the present invention provides a battery, such as Figures 1 to 6 As shown, the battery comprises: a negative electrode sheet 1, comprising a negative electrode current collector 11, and a negative electrode active layer 12 located on at least one side of the negative electrode current collector 11, the negative electrode active layer 12 comprising a second coating 122, and a first coating 121 located between the negative electrode current collector 11 and the second coating 122, the first coating 121 comprising a first active material, the first active material comprising a silicon-carbon material, the second coating 122 comprising a second active material, the second active material comprising a second graphite; a separator 3, comprising a base film 32, and a ceramic layer 31 located on a side of the base film 32 facing the negative electrode sheet 1, the ceramic layer 31 comprising a ceramic material; an average particle size D3 of the second graphite in the second coating 122, and an average particle size D4 of the ceramic material. 31 Satisfies: 3≤D3 / D 31 ≤350, the thickness H of the ceramic layer 31 31 Satisfy 0.5μm≤H 31 ≤6μm.
[0024] According to the research and analysis of the inventors, the lithium insertion potential of silicon-carbon material is higher than that of graphite. During the charging process, graphite particles are first inserted into lithium, and silicon-carbon material particles are inserted into lithium later, so as to achieve the effect of shallow charging and shallow discharging of silicon-carbon material particles. In the embodiment of the present invention, silicon-carbon material is added to the first coating 121 close to the negative electrode current collector 11 (that is, the lower layer close to the negative electrode current collector 11 in the double coating of the negative electrode sheet 1), and the average particle size D3 of the graphite in the second coating 122 and the thickness H of the ceramic layer 31 are coordinated and controlled. 31 , the average particle size D of ceramic materials 31 , so that it satisfies 3≤D3 / D 31 ≤350、0.5μm≤H 31 ≤6μm, in such a battery system, the silicon-carbon particles (i.e., silicon-carbon materials) can play a shallow charge and shallow discharge effect, reduce the side reactions on the surface of the silicon-carbon particles, and reduce the expansion of the silicon-carbon particles, thereby improving the energy density while alleviating the large extension (or expansion) of the negative electrode sheet (silicon-doped negative electrode) 1 caused by the expansion of the silicon-carbon particles, avoiding the problem of electrode sheet breakage and battery failure; at the same time, a ceramic diaphragm 3 is used (i.e., at least one side surface of the base film 32 of the diaphragm 3 has a ceramic layer 31), and by synergistically regulating the average particle size D3 of the graphite in the second coating 122 and the average particle size D4 of the ceramic material in the ceramic layer 31 31 , and the thickness H of the ceramic layer 31 31 When the above range is met, the extension of the electrode coating can be restrained by the diaphragm 3, the risk of electrode breakage can be reduced, and the battery expansion rate can be reduced, while improving the battery's capacity and cycle stability and other performance, avoiding problems such as battery failure caused by electrode breakage.
[0025] If the ceramic layer 31 in the diaphragm 3 is too thin (H 31 <0.5μm), then the average particle size D3 of the graphite in the second coating 122 and the average particle size D 31 The adaptability is poor, which is not conducive to the role of the diaphragm in binding the extension of the electrode coating. If the ceramic layer 31 is too thick (H 31 >6μm), it will occupy more space and affect the energy density of the battery. Therefore, by collaboratively controlling 3≤D3 / D 31 ≤350、0.5μm≤H 31 ≤6μm, which can reduce the risk of electrode short circuit and battery expansion rate, while also improving battery capacity and cycle stability.
[0026] For example, the thickness H of the ceramic layer 31 is 31The thickness may be 0.5 μm, 1 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, or a range consisting of any two of them.
[0027] For example, D3 / D 31 It can be 3, 4, 7, 10, 25, 55, 65, 70, 90, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 335, 350 or a range consisting of any two of them.
[0028] In some embodiments, 4≤D3 / D 31 ≤70, which is conducive to further reducing the risk of electrode breakage and inhibiting the battery expansion rate, while maintaining a higher battery capacity.
[0029] In some embodiments, 5 μm ≤ D3 ≤ 22 μm, D3 is, for example, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 22 μm, or any two thereof. In the above-mentioned negative electrode system with a double-layer coating, under the control of 3 ≤ D3 / D 31 ≤350、0.5μm≤H 31 On the basis of ≤6μm, by further controlling 5μm≤D3≤22μm, it is more conducive to the capacity of the second coating 122 and improve the battery capacity. At the same time, it cooperates with the first coating 121 and the diaphragm 3 and other components to reduce the risk of electrode breakage and reduce the battery expansion rate.
[0030] In some embodiments, 50 nm ≤ D 31 ≤2μm, D 31 For example, it is 50nm, 100nm, 150nm, 180nm, 190nm, 200nm, 210nm, 220nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.3μm, 1.5μm, 1.8μm, 2μm or any two thereof. In the above-mentioned negative electrode system with a double-layer coating, under the control of 3≤D3 / D 31 ≤350、0.5μm≤H 31 Based on ≤6μm, by further controlling 50nm≤D 31 ≤2μm, which is beneficial to further ensure the function of the ceramic layer 31, assist in restraining the extension of the pole piece through the diaphragm 3, reduce the risk of pole piece breakage, and at the same time maintain a high energy density of the battery and improve the battery's capacity and other performance.
[0031] In some specific embodiments, the average particle size D of the ceramic material is31 It may be in the range of 180 to 500 nm, such as 180 to 220 nm, for example 180 nm, 190 nm, 200 nm, 210 nm, 220 nm or a range consisting of any two of them.
[0032] Specifically, the ceramic material in the ceramic layer 31 may include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, titanium oxide, barium sulfate, and calcium sulfate.
[0033] According to the inventor's research, the present invention mainly controls the average particle size D of the ceramic layer 31. 31 , so that it matches the particle size D3 of the second graphite, satisfying 3≤D3 / D 31 ≤350, and cooperate with 0.5μm≤H 31 ≤6μm, the risk of pole piece fracture is reduced, battery expansion is suppressed, and battery capacity and cycle stability are improved. The above ceramic materials can be used in the ceramic layer 31 to achieve this effect. 31 ≤2μm, which is beneficial to further ensure the function of the ceramic layer 31, assist in restraining the extension of the pole piece through the diaphragm 3, reduce the risk of pole piece breakage, and at the same time maintain a high energy density of the battery and improve the battery's capacity and other performance.
[0034] In addition, the ceramic layer 31 also includes a binder. The binder in the ceramic layer 31 is used to bond ceramic material particles and can improve the adhesion between the ceramic layer 31 and film layers such as the base film 32. The binder in the ceramic layer 31 can include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polymethyl methacrylate (PMMA).
[0035] In some embodiments, the mass percentage of the ceramic material in the ceramic layer 31 (i.e., the ratio of the mass of the ceramic material to the total mass of the ceramic layer 31) can be 50% to 99.8%, for example, 50%, 60%, 70%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 97%, 99.5%, 99.8% or a range consisting of any two of them.
[0036] Specifically, the negative electrode active layer 12 includes a negative electrode active material, and the above-mentioned first coating 121 and the second coating 122 each include a negative electrode active material, the negative electrode active material in the first coating 121 is called a first active material, and the negative electrode active material in the second coating 122 is called a second active material. The first active material in the first coating 121 includes a silicon-carbon material, and the second active material in the second coating 122 includes a second graphite (the graphite in the second coating 122 is called the second graphite), wherein the second coating 122 may not include silicon-based materials such as silicon carbon, that is, the content of silicon-based materials such as silicon carbon in the second coating 122 is substantially 0.
[0037] In addition, the first active material in the first coating 121 also includes a first graphite (the graphite in the second coating 122 is called a second graphite), which is beneficial to further reduce the expansion rate of the battery and improve the battery's cycle life and other performance.
[0038] In some embodiments, the average particle size (Dv50) D2 of the first graphite in the first coating 121 is greater than the average particle size (Dv50) D3 of the second graphite in the second coating 122, preferably 0.3<D3 / D2<1, for example, D3 / D2 can be 0.31, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two thereof. In this way, the first graphite in the first coating 121 has a relatively larger particle size. In the above-mentioned negative electrode system with a double-layer coating, by further synergistically regulating the average particle size D3 of the second graphite in the second coating 122 and the average particle size D2 of the first graphite in the first coating 121, so that they satisfy the above relationship, it is more conducive to the adaptation of the first coating 121 and the second coating 122, and further takes into account maintaining the function of the negative electrode active layer 12 and reducing the expansion problem of the negative electrode active layer 12, thereby further reducing the cycle expansion rate of the battery while maintaining a higher capacity of the battery and reducing the risk of electrode breakage.
[0039] In some embodiments, the average maximum particle size D1 of the silicon-carbon material in the first coating 121 and the average particle size (Dv50) D2 of the first graphite in the first coating 121 satisfy 0.5≤D1 / D2≤1.5, for example, D1 / D2 can be 0.5, 0.6, 0.7, 0.9, 1.0, 1.1, 1.3, 1.4, 1.5 or a range consisting of any two of them. In the above-mentioned negative electrode system with a double-layer coating, by further synergistically regulating the average maximum particle size D1 of the silicon-carbon material in the first coating 121 and the average particle size D2 of the first graphite in the first coating 121 so as to satisfy the above relationship, it is beneficial to introduce silicon-carbon material into the first coating 121 to improve the energy density of the negative electrode sheet 1, while further inhibiting the expansion of the negative electrode sheet 1, reducing the cycle expansion rate of the battery, and reducing the risk of electrode sheet breakage.
[0040] In some embodiments, 5 μm≤D1≤20 μm, where D1 is, for example, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, or a range consisting of any two thereof.
[0041] The average maximum particle size D1 of the silicon-carbon material in the above-mentioned first coating 121 can be tested by the following process: use argon ions to cut the negative electrode sheet 1 to obtain the cross-sectional morphology, measure the maximum size of the silicon-carbon particles seen in 3-5 cross sections at 1K times, take the average value, and obtain the average maximum particle size D1 of the silicon-carbon material (i.e., silicon-carbon particles).
[0042] In the embodiment of the present invention, the average particle size of the material (such as the average particle size D2 of the first graphite, the average particle size D3 of the second graphite, the average particle size D 31 The particle size (e.g., particle size distribution) can be measured by conventional methods in the art, such as by a laser particle size analyzer or by electron microscopy testing and statistics such as a scanning electron microscope (SEM).
[0043] In specific implementation, when testing the average particle size D2 of the first graphite in the first coating 121, the first coating 121 can be scraped off the negative electrode sheet 1, and the obtained first coating 121 material is dispersed in a solvent such as water, and evenly dispersed by ultrasound or the like (specifically, ultrasound can be used for at least 2 minutes) to remove components such as binders on the surface of particles in the first coating 121121 material, and then the particle size Dv50 of the particles is tested by a laser particle size analyzer, which is the average particle size D2 of the first graphite in the first coating 121.
[0044] In addition, when testing the average particle size D3 of the second graphite in the second coating 122, the second coating 122 can be scraped off the negative electrode sheet 1, and the obtained second coating 122 material can be dispersed in a solvent such as water, and evenly dispersed by ultrasound or the like (specifically, ultrasound can be used for at least 2 minutes) to remove components such as binders on the surface of particles in the second coating 122 material, and then the particle size Dv50 of the particles is tested by a laser particle size analyzer, which is the average particle size D3 of the second graphite in the second coating 122.
[0045] In addition, the average particle size D of the ceramic material in the ceramic layer 31 of the test diaphragm 3 is 31 When the ceramic layer 31 of the diaphragm 3 is scanned and analyzed by SEM, the particle size (diameter) of the ceramic material therein can be tested and the average value can be obtained by statistics. The average value obtained is the average particle size D of the ceramic material. 31 Alternatively, the ceramic layer 31 can be scraped off from the diaphragm 3, the obtained ceramic layer 31 material powder is dispersed in a solvent, and then the particle size Dv50 of the ceramic material is measured by a laser particle size analyzer, which is the average particle size D of the ceramic material. 31 .
[0046] In an embodiment of the present invention, the battery includes a battery cell, a shell encapsulating the battery cell, and an electrolyte. The battery cell includes a positive electrode sheet 4, a negative electrode sheet 1, and a separator 3 located between the positive electrode sheet 4 and the negative electrode sheet 1. The electrolyte is injected into the shell to infiltrate the battery cell.
[0047] Specifically, the electrolyte includes a solvent, a solute and an additive. The electrolyte may be a non-aqueous electrolyte, wherein the solvent may include an organic solvent, and may specifically include a carbonate solvent, for example, one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and propyl propionate (PP); the additive may include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), and sulfonate; the solute may include a lithium salt, and the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.
[0048] Among them, the sulfonate ester may specifically include 1,3-propane sultone (PS) and / or 1,3-propylene sultone (PST). Both PS and PTS can be used as high-temperature film-forming additives to improve the high-temperature cycle performance of the battery. At the same time, they are adapted to the above-mentioned negative electrode system with a double-layer coating to further inhibit battery expansion, while improving the battery's capacity and cycle stability and other performance.
[0049] In some embodiments, the electrolyte includes sulfonates (such as PS and / or PST), which is more compatible with the negative electrode sheet 1 having the first coating 121 and the second coating 122 and the ceramic diaphragm 3, further taking into account reducing the cycle expansion rate of the battery and increasing the battery capacity, and reducing the risk of electrode short circuit.
[0050] The inventors found in their research that the mass percentage content e of the sulfonate in the electrolyte and the tensile strength S1 of the negative electrode current collector 11 can satisfy S1 / e≥550, preferably 550≤S1 / e≤60000, and the unit of S1 is MPa. By synergistically controlling the mass percentage content e of the sulfonate in the electrolyte and the tensile strength S1 of the negative electrode current collector 11 within the above range, the deformation of the negative electrode sheet 1 and the fracture of the positive electrode sheet 4 can be effectively avoided. The reason for this is that the high-temperature film-forming additive (sulfonate) has a certain corrosive effect on the negative electrode current collector 11 (such as copper foil), which will greatly reduce The strength of the negative electrode collector 11 (such as copper foil) of the battery after formation causes the corroded negative electrode collector 11 to lose its binding force on the negative electrode coating (paste) due to insufficient strength, resulting in the negative electrode sheet 1 being easily deformed. The deformed negative electrode sheet 1 will squeeze the positive electrode sheet 4, thereby causing the positive electrode sheet 4 to break. In the above-mentioned negative electrode system with a double-layer coating, by further synergistically controlling the content e of sulfonic acid ester in the electrolyte and the tensile strength S1 of the negative electrode collector 11 to meet the above-mentioned range, it is more conducive to avoiding the deformation of the negative electrode sheet 1 and the breakage of the positive electrode sheet 4, while taking into account the better high-temperature cycle performance of the battery.
[0051] Furthermore, the tensile strength S1 of the negative electrode current collector 11 is ≥400 MPa. Preferably, for example, S1 may be 400 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa, 900 MPa, 1000 MPa or a range consisting of any two of them, which is beneficial to better reduce the risk of fracture of the negative electrode sheet 1 and the positive electrode sheet 4.
[0052] In some embodiments, 200 MPa≤S1≤700 MPa, and further can be 400 MPa≤S1≤700 MPa.
[0053] Furthermore, the mass percentage e of the sulfonic acid ester in the above-mentioned electrolyte can be 0.1% to 20%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, %4%, 5%, 10%, 15%, 20% or a range composed of any two of them, which is beneficial to better balance the high temperature cycle performance and avoid the problem of breakage of the negative electrode sheet 1 and the positive electrode sheet 4.
[0054] In some embodiments, the thickness H of the negative electrode current collector 11 is 10 , the tensile strength S1 of the negative electrode current collector 11, the mass ratio of the silicon-carbon material in the negative electrode active layer 12 to the graphite in the negative electrode active layer 12 (ie, the silicon doping amount of the negative electrode active layer 12) X satisfies (H 10 ×S1) / X≥1600, preferably 1600≤(H 10×S1) / X≤660000, where S1 is measured in MPa, can effectively avoid the problem of the negative electrode sheet 1 being broken. The reason for this is that as the silicon doping amount X increases, the negative electrode coating expands more during the charge and discharge process, causing the negative electrode sheet 1 to extend more, and the negative electrode sheet 1 is more likely to break. By increasing the tensile strength S1 (such as the maximum tensile force) of the negative electrode collector 11 (such as copper foil), the problem of the negative electrode sheet 1 being easy to break can be effectively avoided. At the same time, the thickness of the negative electrode collector 11 (such as copper foil) can be increased to increase the maximum tensile force it can withstand, which is more conducive to avoiding the problem of the negative electrode sheet 1 being easy to break. Therefore, in the above-mentioned negative electrode system with a double-layer coating, a silicon-carbon material is introduced into the first coating 121, and 3≤D3 / D is controlled. 31 ≤350、0.5μm≤H 31 ≤6μm, on this basis, by synergistically regulating the thickness H of the negative electrode current collector 11 10 , the tensile strength S1 of the negative electrode current collector 11 and the silicon doping amount X meet the above ranges, which can further avoid the problem of fracture of the negative electrode sheet 1.
[0055] For example, when the graphite in the negative electrode active layer 12 exists in the first coating layer 121 and the second coating layer 122, or the negative electrode active layer 12 is composed of the first coating layer 121 and the second coating layer 122, the silicon doping amount X = the mass of the silicon-carbon material in the first coating layer 121 / (the mass of the first graphite in the first coating layer 121 + the mass of the second graphite in the second coating layer 122).
[0056] For example, (H 10 ×S1) / X can be 1600, 2000, 2500, 5000, 10000, 100000, 500000, 660000 or a range consisting of any two of them.
[0057] In some embodiments, 3 μm ≤ H 10 ≤12μm, H 10 For example, the range is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or a combination of any two thereof.
[0058] In the embodiment of the present invention, the diaphragm 3 is located between the positive electrode sheet 4 and the negative electrode sheet 1, and the diaphragm 3 is bonded to the positive electrode sheet 4 and the negative electrode sheet 1 respectively (that is, one side of the diaphragm 3 is bonded to the positive electrode sheet 4, and the other side is bonded to the negative electrode sheet 1). In specific implementation, the positive electrode sheet 4, the diaphragm 3 and the negative electrode sheet 1 can be placed in sequence and hot pressed to be hot pressed together.
[0059] Specifically, the battery cell can be a wound battery cell (wound core), that is, the positive electrode sheet 4 and the negative electrode sheet 1 each have a wound structure. The positive electrode sheet 4 includes a plurality of first straight portions and a first bending portion connected between two adjacent first straight portions. The number of the first bending portions is usually at least one, and can be multiple. The positive electrode sheet 4 is bent through the first bending portion to form a wound structure; the negative electrode sheet 1 includes a plurality of second straight portions and a second bending portion connected between two adjacent second straight portions. The number of the second bending portions is usually at least one, and can be multiple. The negative electrode sheet 1 is bent through the second bending portion to form a wound structure.
[0060] In specific implementation, the positive electrode sheet 4, the separator 3 and the negative electrode sheet 1 can be placed in sequence to form a stacked structure (such as Figure 6 As shown in the figure, the positive electrode sheet 4, the separator 3 and the negative electrode sheet 1 are wound and then hot-pressed to form a wound battery cell.
[0061] Generally, a coating layer is provided on the surface of the diaphragm 3, and the coating layer is the surface layer of the diaphragm 3 (for any side surface of the base film 32, when it is provided with a ceramic layer 31, the coating layer is provided on the surface of the ceramic layer 31 (that is, the ceramic layer 31 is located between the base film 32 and the coating layer); when it is not provided with a ceramic layer 31, the coating layer is provided on the surface of the base film 32), and the diaphragm 3 is bonded to the positive and negative electrode sheets 1 through the coating layer on its surface.
[0062] In the embodiment of the present invention, Figure 6 As shown, the ceramic layer 31 of the diaphragm 3 can be specifically located on the side of the base film 32 facing the negative electrode sheet 1, while the ceramic layer 31 is not arranged on the side of the base film 32 facing the positive electrode sheet 4, that is, the diaphragm 3 used is a single-sided ceramic diaphragm 3, specifically a single-sided ceramic double-sided glue-coated diaphragm 3 (that is, the opposite sides of the diaphragm 3 are respectively provided with a glue layer).
[0063] In an embodiment of the present invention, the base film 32 can be a polypropylene (PP) membrane 3, a polyethylene (PE) membrane 3, a polypropylene / polyethylene (PP / PE) double-layer composite film, a polyimide electrospinning membrane 33 (PI), a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite film, or a cellulose non-woven fabric membrane 3 and other conventional membrane 3 materials in the field.
[0064] In some embodiments, the bonding force between the above-mentioned diaphragm 3 and the positive electrode sheet 4 is greater than the bonding force between the diaphragm 3 and the negative electrode sheet 1, which can effectively reduce the risk of the positive electrode sheet 4 breaking. The reason is that during the expansion-contraction process of the battery cell during charge and discharge, the current collector (positive electrode current collector or negative electrode current collector 11) forms a binding force on the positive electrode coating or the negative electrode coating (paste), and the current collector will stretch and extend with the paste. Under normal circumstances, the tensile strength of the diaphragm 3 is greater than the strength of the negative electrode current collector 11 (such as copper foil) and the strength of the positive electrode current collector (such as aluminum foil). Therefore, during the expansion-contraction process of the battery cell during charge and discharge, the positive electrode sheet 4 is more likely to break. In the battery system of the embodiment of the present invention, the negative electrode active layer 12 of the negative electrode sheet 1 includes a first coating 121 and a second coating 122, and the particle size D3 of the second graphite in the second coating 122 of the negative electrode sheet 1 and the average particle size D3 of the ceramic material in the ceramic layer 31 of the diaphragm 3 are synergistically regulated. 31 , the thickness H of the ceramic layer 31 31 Satisfy 3≤D3 / D 31 ≤350、0.5μm≤H 31 ≤6μm, on this basis, by making the bonding force between the diaphragm 3 and the positive electrode sheet 4 greater than the bonding force between the diaphragm 3 and the negative electrode sheet 1, the diaphragm 3 helps to restrain the extension of the positive electrode coating (paste), thereby reducing the risk of breakage of the positive electrode sheet 4, which is beneficial to further improve the battery's capacity and cycle stability and other performance, and avoid problems such as battery failure caused by electrode sheet breakage.
[0065] The positive electrode sheet 4 further includes a positive electrode current collector (such as aluminum foil) 41, and a positive electrode active layer (positive electrode coating) 42 located on at least one side of the positive electrode current collector; the positive electrode active layer 42 includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material may include conventional positive electrode active materials in the art, for example, positive electrode lithium-containing active materials, for example, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary materials, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium rich manganese-based materials. At least one of the ternary materials may include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, etc., wherein the chemical formula of lithium cobalt oxide is generally Li f Co g Al j M i O2, wherein 0.95≤f≤1.1 (for example, 0.95≤f≤1.05), 0.94≤g≤0.985, 0.01≤j≤0.04, 0.005≤i≤0.02, and M is a metal element other than aluminum, and may specifically include transition metal elements, for example, one or more of Mg, Ti, Zr, Y, La, Mn, Ni, Fe, etc.
[0066] According to further research by the inventors, due to the high lithium insertion potential of silicon carbon, the potential of the negative electrode increases. Under a constant voltage, the potential of the positive electrode increases accordingly. That is, under the same voltage system, the positive electrode needs to use a material with higher voltage stability. Therefore, in the embodiment of the present invention, the negative electrode active layer 12 of the negative electrode sheet 1 includes a first coating 121 and a second coating 122, and the particle size D3 of the second graphite in the second coating 122 of the negative electrode sheet 1 and the thickness H of the ceramic layer 31 of the separator 3 are coordinated and regulated. 31 , the average particle size D of ceramic materials 31 Satisfy 3≤D3 / D 31 ≤350、0.5μm≤H 31 ≤6μm, on this basis, by doping yttrium element (Y) into the positive electrode active material, the above-mentioned positive electrode active layer contains yttrium element (Y). Under the same voltage system, yttrium element doping can stabilize the lattice structure of the inner core of the positive electrode active material (such as lithium cobalt oxide, LCO), thereby improving the cycle stability of the positive electrode active material (such as lithium cobalt oxide) at higher voltage and higher temperature, and can also improve the rate performance of the battery.
[0067] In some embodiments, the first coating 121 further includes a first graphite, 400≤y / X≤200000, y is the yttrium doping amount in the positive electrode active layer, the yttrium doping amount is the concentration of the yttrium element in the standard solution measured according to the test method in GBT 30902-2014, and the specific test process can be seen in the test method part of the specific embodiment below, y is in ppm, X is the silicon doping amount of the negative electrode active layer 12, and the yttrium doping amount in the positive electrode active layer and the silicon doping amount X of the negative electrode active layer 12 meet the above relationship range by coordinated regulation, which is conducive to better improving the energy density, cycle stability, rate performance, etc. of the battery. Exemplarily, y / X can be 400, 600, 1000, 5000, 10000, 50000, 100000, 200000 or a range consisting of any two of them.
[0068] In some embodiments, 100 ppm≤y≤2000 ppm, and y is, for example, 100 ppm, 300 ppm, 500 ppm, 800 ppm, 1000 ppm, 1300 ppm, 1500 ppm, 1800 ppm, 2000 ppm, or a range consisting of any two thereof.
[0069] The inventors have found that during the charge and discharge process, the silicon-doped negative electrode will undergo a violent expansion-contraction process, forming an extrusion stress on the positive electrode sheet 4. In order to avoid the positive electrode sheet 4 from breaking, the thickness H of the positive electrode current collector is adjusted by coordinating the 20 , the tensile strength S2 of the positive electrode current collector, and the silicon doping amount X of the negative electrode active layer 12 satisfy (H 20 ×S2) / X≥600, preferably 600≤(H20 ×S2) / X≤300000, which can effectively avoid the breakage of the positive electrode plate and improve the battery's capacity and cycle life.
[0070] For example, (H 20 ×S2) / X can be 600, 1000, 5000, 10000, 50000, 100000, 150000, 200000, 250000, 300000 or a range consisting of any two of them.
[0071] In some embodiments, 50 MPa≤S2≤300 MPa, and S2 is, for example, 50 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, or a range consisting of any two thereof.
[0072] In some embodiments, 5 μm ≤ H 20 ≤20μm, H 20 The thickness may be in the range of 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, or any two thereof.
[0073] In some embodiments, the silicon doping amount X of the negative electrode active layer 12 and the mass percentage a of the silicon element in the silicon carbon satisfy 0.35%≤a×X≤35%, which helps to better reduce the risk of fracture of the negative electrode sheet 1 and the positive electrode sheet 4 while taking into account a higher energy density. Exemplarily, a×X can be 0.35%, 0.5%, 1%, 10%, 15%, 20%, 25%, 35% or a range consisting of any two of them.
[0074] In some embodiments, the mass percentage a of the silicon element in the silicon carbon is 35% to 70%, for example, 35%, 40%, 50%, 60%, 70% or any two thereof. Relatively speaking, the use of low-silicon materials has a lower silicon content, so the expansion rate of the low-silicon materials is low, and more silicon-carbon materials can be added to the negative electrode sheet 1, which is beneficial to improve the capacity and cycle performance of the negative electrode sheet 1.
[0075] In some embodiments, the silicon content in the above-mentioned silicon carbon (silicon carbon material particles) tends to decrease from the center of the silicon carbon to the edge of the silicon carbon, that is, the silicon content in the center of the silicon carbon particles is greater than the silicon content on the surface of the silicon carbon particles. By adopting this silicon carbon material, it is beneficial to improve the rate charging performance and reduce the expansion of the particles, which helps to better reduce the risk of electrode breakage.
[0076] Specifically, Figure 4This is an electron microscope image of silicon carbon (low-silicon material particles) of an embodiment under the backscattered electron mode (BSE mode). The main component of the black part is carbon, and the main component of the white part is silicon. It can be seen that there are areas with different substrates (contrast) inside the silicon-carbon material (low-silicon material particles). The silicon content is high at the edge (surface) of the silicon-carbon particle and low in the middle (center).
[0077] The embodiments of the present invention can obtain the above-mentioned silicon-carbon material by conventional methods in the art, for example, it can be commercially purchased or homemade by conventional methods in the art. For example, the above-mentioned silicon-carbon material in which the silicon content tends to decrease from the center of the silicon-carbon to the edge of the silicon-carbon can include an inner core and a carbon coating layer present on the surface of the inner core, and the inner core includes a porous carbon substrate and silicon elements dispersed in the porous carbon substrate. The silicon elements can be specifically dispersed inside the pores of the porous carbon substrate.
[0078] In some embodiments, the silicon doping amount X may be 1% to 50%, such as 1%, 10%, 20%, 30%, 40%, 50% or a range consisting of any two thereof, preferably 4% to 30%.
[0079] like Figures 1 to 3 As shown, the surface of the second coating 122 of the above-mentioned negative electrode sheet 1 is provided with a recess 13, which is beneficial to further improve the electrochemical performance and safety performance of the battery. The reason for this is that when the surface of the second coating 122 is provided with a recess 13, it is beneficial to guide the electrolyte, so that the electrolyte can more fully infiltrate the battery cell, increase the electrolyte storage capacity of the battery cell, thereby improving the migration ability of active ions such as lithium ions, improve conductivity, reduce voltage drop, and reduce the risk of short circuit.
[0080] In some embodiments, the width L of the concave portion 13 is 50 μm to 160 μm, for example, 50 μm, 80 μm, 100 μm, 150 μm, 160 μm or a range consisting of any two thereof.
[0081] Specifically, the surface of the second coating 122 may be provided with a concave portion 13 (ie, the concave portion 13 is continuously provided on the surface of the second coating 122), or, as Figures 1 to 3 As shown, the surface of the second coating 122 is provided with at least two recesses 13, and these recesses 13 can be distributed along the first direction b (such as Figure 2 As shown), or distributed along the second direction c, or part of the recesses 13 are distributed along the first direction b and part of the recesses 13 are distributed along the second direction c (as shown Figure 1 shown).
[0082] Among them, Figures 1 to 3As shown, at least part of the recesses 13 are distributed along the first direction b, two adjacent recesses 13 in the first direction b are separated by the second coating 122, and the spacing between two adjacent recesses 13 in the first direction b (i.e., the distance between two adjacent recesses 13 in the first direction b) △L>0.
[0083] Specifically, the surface of the second coating 122 may include at least one group of recess groups 130, each group of recess groups 130 includes at least two recesses 13 distributed along the first direction b, and when the number of recess groups 130 is at least two (i.e., the surface of the second coating 122 includes at least two groups of recess groups 130), these recess groups 130 are distributed along the second direction c.
[0084] For example, Figure 1 As shown, the surface of the second coating 122 includes two groups of recessed portions 130, which are distributed along the second direction c. In each recessed portion group 130, one side edge of the recessed portion 13 in the length direction is substantially flush with one side edge of the second coating 122 in the width direction; or Figure 2 As shown, the surface of the second coating layer 122 has a group of recesses 130 , wherein the length of the recesses 13 in the second direction c is substantially equal to the width of the second coating layer 122 .
[0085] In some embodiments, in two adjacent recess groups 130, a distance w between a recess 13 in one recess group 130 and a recess 13 in another recess group 130 in the second direction c basically satisfies the following relationship: width of the first coating = length of a recess 13 in one recess group 130 in the second direction c + length of a recess 13 in another recess group 130 in the second direction c + w.
[0086] Among them, in two adjacent recess groups 130, the recess 13 in one recess group 130 may be connected or not connected with the recess 13 located in the other recess group 130 and closest to the recess 13. When the two recesses 13 are connected, the gap (the distance in the second direction c) w between the two recesses 13 is basically equal to 0.
[0087] Continue to refer Figures 1 to 3 , the spacing △L between two adjacent recesses 13 in the first direction b is greater than 0, the second coating 122 has a first side 101 and a second side 102 relative to each other in the first direction b, the distance between the recess 13 closest to the outer edge of the first side 101 of the second coating 122 and the outer edge of the first side 101 of the second coating 122 is recorded as △L1, and the distance between the recess 13 closest to the outer edge of the second side 102 of the second coating 122 and the outer edge of the second side 102 of the second coating 122 is recorded as △L2, so that the recesses 13 are arranged on the entire surface of the second coating 122 at a spacing of △L.
[0088] The interval ΔL between two adjacent recesses 13 in the first direction b refers to the distance between the two adjacent recesses 13 in the first direction b, which is also the interval between two adjacent recesses 13 in each recess group 130 .
[0089] In some embodiments, the interval ΔL between two adjacent recesses 13 in the first direction b is 0.3-3 mm, for example, 0.3 mm, 0.5 mm, 1 mm, 2 mm, 3 mm or a range consisting of any two thereof.
[0090] Continue to refer Figures 1 to 3 The width direction of the recesses 13 is substantially parallel to the first direction b, and the length direction (extension direction) of the recesses 13 is substantially perpendicular to the first direction b.
[0091] Specifically, the recess 13 may be in the shape of a hole or a groove, and preferably the recess 13 is a linear groove, that is, the projection of the recess 13 on the negative electrode current collector 11 is in the shape of a strip (eg Figure 1 and Figure 2 ), which may be a rectangle (as shown in Figure 2 as shown) or other regular or irregular shapes.
[0092] Continue to refer Figure 1 and Figure 2 When at least two recesses 13 are provided on the surface of the second coating 122, each recess 13 is a linear groove, and its projection on the negative electrode current collector 11 is basically a rectangle. The length directions (extension directions) of these recesses 13 are basically parallel to each other, specifically parallel to the second direction c, and the width directions of these recesses 13 are basically parallel, basically parallel to the first direction b.
[0093] In the embodiment of the present invention, a laser can be used to punch a recess 13 of a preset shape and parameters such as thickness, width, length and spacing on the surface of the negative electrode active coating 12. For example, a recess 13 (linear groove) can be formed on the surface of the second coating 122 by laser punching. Specifically, the thickness and other parameters of the recess 13 formed can be adjusted by adjusting parameters such as the laser intensity. These control methods are conventional operations in the field and will not be repeated here.
[0094] Specifically, the first direction b and the second direction c intersect, and the two may be perpendicular to each other. Figure 1 and Figure 2 As shown, the second direction c, the length direction of the recess 13, the width direction of the second coating 122, the width direction of the negative electrode collector 11, and the width direction of the negative electrode sheet 1 are basically parallel to each other, and the first direction b, the width direction of the recess 13, the length direction of the second coating 122, the length direction of the negative electrode collector 11, and the length direction of the negative electrode sheet 1 are basically parallel to each other.
[0095] In addition, if Figure 3 As shown, the recess 13 extends from the surface of the second coating 122 to the inside of the second coating 122, and the depth direction of the recess 13 can be basically parallel to the third direction d, and the third direction d, the thickness direction of the second coating 122, the thickness direction of the negative electrode collector 11, the thickness direction of the negative electrode sheet 1, and the thickness direction of the separator 3 are parallel to each other.
[0096] In general, if Figure 3 As shown, the depth h of the recess 13 is less than the thickness of the second coating 122 , that is, the recess 13 does not penetrate the second coating 122 in the thickness direction of the second coating 122 , that is, the second coating 122 exists between the recess 13 and the negative electrode current collector 11 .
[0097] In some embodiments, the depth h of the recess 13 is 3 μm to 40 μm, for example, 3 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm or a range consisting of any two thereof.
[0098] In addition, the negative electrode sheet 1 further includes a negative electrode tab 14, and the battery further includes a tab tape 2 connected to the negative electrode tab. The tab tape 2 can be provided on the negative electrode sheet 1 in an embedded manner, which is beneficial to reducing the thickness of the negative electrode sheet 1 and further improving the energy density and other performance of the battery. Specifically, the negative electrode active layer 12 located at least on one side of the surface of the negative electrode current collector 11 is provided with a slot, the negative electrode tab 14 is provided at the slot, and the tab tape 2 is provided on the side of the negative electrode tab 14 away from the negative electrode current collector 11 and embedded in the slot.
[0099] In some specific embodiments, Figure 5 As shown, in the negative electrode active layer 12 on the surface of one side (hereinafter referred to as the third side) of the negative electrode current collector 11, its groove includes a main area 127, a first recessed area (ear groove) 123, and a second recessed area 124 located between the main area 127 and the first recessed area 123, and the negative electrode ear 14 is arranged in the first recessed area 123; the ear tape 2 includes a first connecting portion 21 located on the side of the negative electrode ear 14 away from the negative electrode current collector 11, and a second connecting portion 22 located on the side of the first recessed area 123 away from the negative electrode current collector 11, and the side surface of the second connecting portion 22 away from the negative electrode current collector 11 does not exceed the side surface of the main area 127 away from the negative electrode current collector 11.
[0100] Specifically, the negative electrode active layer 12 is substantially absent in the first recessed area 123, that is, the first recessed area 123 exposes the surface of the negative electrode current collector 11, and the negative electrode tab 14 can be welded to the negative electrode current collector exposed in the first recessed area 123. The negative electrode active layer 12 is present in the second recessed area 124, and the depth of the second recessed area 124 is less than the depth of the first recessed area 123.
[0101] In addition, the width W2 of the tab tape 2 is greater than the width W1 of the first recessed area 123, the width of the groove is greater than the width of the tab tape 2 (the width of the groove is basically equal to the sum of the width W1 of the first recessed area 123 and the width of the second recessed area 124), the depth of the second recessed area 124 is greater than or equal to the thickness of the tab tape, and the deepest depth of the groove (also the depth of the first recessed area 123) is less than the thickness of the negative electrode active layer 12.
[0102] In some embodiments, the width W1 of the first recessed area 123 can be 6 to 15 mm, the width W2 of the tab tape 2 can be 7 to 20 mm, the width W3 of the groove can be 8 to 25 mm, and the depth of the groove can be greater than or equal to 5 μm, for example, about 20 μm, so that the tab tape can be embedded in the groove.
[0103] In addition, if Figure 5 As shown, in the negative electrode active layer 12 on the other side (hereinafter referred to as the fourth side) of the negative electrode current collector 11, there are also grooves corresponding to the grooves on the third side surface, that is, the projections of the grooves on the fourth side surface and the grooves on the third side surface on the negative electrode current collector 11 at least partially overlap, generally basically completely overlap, and the grooves on the fourth side surface include a third recessed area 125 corresponding to the first recessed area 123, and a fourth recessed area 126 corresponding to the second recessed area 124.
[0104] In the embodiment of the present invention, the battery may be a lithium-ion battery.
[0105] In the embodiment of the present invention, any negative electrode coating (such as the first coating 121 or the second coating 122) may further include a conductive agent and a binder.
[0106] Specifically, the binder in the positive electrode active layer and the negative electrode coating (such as the first coating 121 or the second coating 122) can be a conventional binding material in the art, for example, one or more of polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile (PAN), polyacrylate, polyacrylic acid (PAA), polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene and styrene-butadiene rubber (SBR), and the polyacrylate may include lithium polyacrylate and / or sodium polyacrylate, etc.
[0107] In the embodiment of the present invention, the conductive agent in the positive electrode active layer and the negative electrode coating can be a conventional bonding material in the art, for example, one or more of carbon nanotubes (CNTs), carbon black (SP), acetylene black, graphene, and conductive graphite.
[0108] In addition, the negative electrode coating may further include a thickener, which may include a carboxymethyl cellulose (CMC)-based thickener, such as carboxymethyl cellulose and / or carboxymethyl cellulose salts, such as carboxymethyl cellulose lithium (CMC-Li) and / or carboxymethyl cellulose sodium (CMC-Na).
[0109] In general, for any negative electrode coating (such as the first coating 121 or the second coating 122), based on the total mass of the negative electrode coating (negative electrode active material layer), the mass fraction of the negative electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 95%, 99% or any two thereof, and the mass fraction of the conductive agent can be 0.3% to 12%, for example, 0.3%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12% or any two thereof. The mass fraction of the binder can be in the range of 0% to 15%, for example, 0, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two of them, and the mass fraction of the thickener can be in the range of 0.05% to 3%, for example, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two of them, but is not limited to this.
[0110] In addition, based on the total mass of the positive electrode active layer (positive electrode active material layer), the mass fraction of the positive electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 95%, 99% or a range consisting of any two of them, the mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two of them, and the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two of them, but is not limited to this.
[0111] In an embodiment of the present invention, the positive electrode sheet 4 can be prepared by a conventional method in the art such as a coating method. For example, the preparation process of the positive electrode sheet 4 may include: placing materials such as a positive electrode active material, a conductive agent and a binder in a solvent to prepare a positive electrode slurry, and the solvent used includes, for example, N-methylpyrrolidone (NMP), and then applying the positive electrode slurry to at least one surface of the positive electrode collector. After drying, rolling and other processes, a positive electrode active material layer is formed on at least one surface of the positive electrode collector to prepare the positive electrode sheet 4; wherein, during the coating process, a groove (slot position) exposing the surface of the positive electrode collector is retained at a preset position of the positive electrode collector. After the positive electrode active material layer is formed through coating, drying, rolling and other processes, the positive electrode ear is welded to the slot position by laser or ultrasonic welding (the positive electrode ear is welded to the positive electrode collector).
[0112] In the embodiment of the present invention, a negative electrode coating can be formed on the surface of the negative electrode current collector by a conventional method in the art such as a coating method, and then a line is made on the surface of the negative electrode coating by a laser to obtain the negative electrode sheet 1. For example, the process of the negative electrode sheet 1 may include: placing materials such as negative electrode active materials, conductive agents and binders in a solvent to form a negative electrode slurry, the solvent used includes, for example, water (such as deionized water), and then applying the negative electrode slurry to the surface of the negative electrode collector, and after drying, rolling and other processes, a negative electrode active layer is formed on the surface of the negative electrode collector; then, a recess 13 is formed in a preset area on the surface of the negative electrode active material layer by laser drilling to obtain the negative electrode sheet 1; wherein, during the coating process, a groove (slot position) exposing the surface of the negative electrode collector is retained at a preset position of the negative electrode collector, after the negative electrode active material layer is formed by coating, drying, rolling and other processes, and the recess 13 is formed on the surface of the negative electrode active material layer by laser wire drawing and other methods, and then the negative electrode tab is welded at the slot position by laser or ultrasonic welding and other methods (the negative electrode tab is welded to the positive electrode collector) to obtain the negative electrode sheet 1.
[0113] In the embodiment of the present invention, a conventional laser drilling machine in the art is used for laser drilling.
[0114] In an embodiment of the present invention, the battery can be manufactured according to conventional methods in the art. For example, after the positive electrode sheet 4 and the negative electrode sheet 1 are cut into sheets, the positive electrode sheet 4, the separator 3, and the negative electrode sheet 1 are stacked in sequence and hot-pressed together, and then wound to form a roll core, wherein the ceramic layer of the separator 3 faces the negative electrode sheet 1 during winding, and then the shell is used for packaging. After the processes of liquid injection (injecting electrolyte into the shell), formation, capacity division, secondary sealing, sorting and OCV (testing open circuit voltage), the battery is manufactured. These steps / processes are all conventional operations in the art, and the present invention does not impose any special restrictions on this and will not be repeated.
[0115] The present invention is further described below through specific embodiments.
[0116] Example 1
[0117] 1. Preparation of positive electrode
[0118] The positive electrode active material (lithium cobalt oxide LCO), SP, and PVDF are mixed in a mass ratio of 97.6:1.4:1, and NMP is added and stirred evenly to prepare a positive electrode slurry; wherein the yttrium doping amount y in the above-mentioned lithium cobalt oxide LCO is 700ppm; the positive electrode slurry is coated on the front and back surfaces of an aluminum foil with a thickness of 8μm, and the initial tensile strength of the aluminum foil is 290MPa. After baking and rolling, a positive electrode active material layer is formed on the front and back surfaces of the aluminum foil to obtain a positive electrode sheet with a thickness of about 80μm;
[0119] A slot exposing the surface of the aluminum foil is retained at a preset tab position of the aluminum foil, and after the positive electrode active material layer is formed, the positive electrode tab is welded in the slot by laser or ultrasonic welding (i.e., the positive electrode tab and the aluminum foil exposed through the slot are welded) to obtain a positive electrode sheet.
[0120] 2. Preparation of negative electrode sheet
[0121] (1) The first negative electrode active material, SP, CMC-Li, and PAA are mixed in a mass ratio of 97:0.4:0.1:2.5, and deionized water is added to prepare a first negative electrode slurry; wherein the first active material includes a first graphite and a silicon-carbon material, and the silicon content in the silicon-carbon particles increases from the center of the silicon-carbon to the edge of the silicon-carbon (the electron microscope image of the silicon-carbon in the backscattered electron mode (BSE mode) is as follows: Figure 4 shown);
[0122] (2) mixing the second negative electrode active material, SP, CMC-Li, and PAA in a mass ratio of 97:0.4:0.1:2.5, and adding deionized water to prepare a second negative electrode slurry; wherein the second active material is a second graphite;
[0123] (3) using a double-layer coating method, the first negative electrode slurry and the second negative electrode slurry are simultaneously coated on the front and back surfaces of a carbon-coated copper foil having a thickness of 4 μm (during coating, the extrusion head for coating the second negative electrode slurry is located above the extrusion head for coating the first negative electrode slurry, so that the first coating layer formed by the first negative electrode slurry is located between the carbon-coated copper foil and the second coating layer formed by the second negative electrode slurry), and after baking and rolling, a negative electrode active layer is formed on the front and back surfaces of the carbon-coated copper foil (the negative electrode active layer includes the second coating layer and the first coating layer located between the carbon-coated copper foil and the second coating layer);
[0124] Among them, a slot for exposing the surface of the aluminum foil is reserved at the preset tab position of the carbon-coated copper foil. After the negative electrode active layer is formed, the negative electrode tab is welded in the slot by laser or ultrasonic welding, and the tab adhesive paper attached to the surface of the negative electrode tab is arranged on the negative electrode sheet in an embedded manner (see the tab adhesive paper arrangement method). Figure 5 , no longer described), wherein the width of the groove W3 = 13mm, the width of the tab tape W2 = 12mm, the width of the first recessed area 123 W1 = 9mm, the thickness of the tab tape is 12μm, and the groove depth is 20μm.
[0125] (4) A linear groove (i.e., a concave portion that does not penetrate the negative electrode active material layer) is punched on the surface of each side of the negative electrode active material layer using a laser, with a concave spacing ΔL = 1.5 mm, a concave width L = 100 μm, and a concave depth h = 20 μm, to obtain a negative electrode sheet with a thickness of about 100 μm (the structural schematic diagram of the negative electrode sheet is shown in FIG. Figure 1 and Figure 3 As shown, no further description is given here).
[0126] 3. Preparation of batteries
[0127] The positive electrode sheet and the negative electrode sheet are cut into pieces according to a preset shape and size; then, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, wound, and hot-pressed together to obtain a winding core; wherein the separator includes a base film, a ceramic layer located on the side of the base film facing the negative electrode sheet, a rubber layer located on the side of the ceramic layer facing the negative electrode sheet, and a rubber layer located on the side of the base film facing the positive electrode sheet, the thickness of the rubber layer on one side is about 1 μm, the material of the rubber layer is PVDF, the thickness of the base film is 5 μm, and the thickness of the ceramic layer is H 31 The average particle size D of the ceramic material is 2 μm. 31 The thickness is 200 nm, and the ceramic layer is composed of ceramic particles (boehmite) and a third binder (PVDF) in a mass ratio of 99.5:0.5;
[0128] Then, the roll core is packaged with aluminum-plastic film, and then after baking, electrolyte injection, formation, secondary sealing, sorting and OCV processes, a lithium-ion battery with a thickness of 5.285 mm is obtained; wherein the lithium salt in the electrolyte used is LiPF6, and its concentration is 1 mol / L, and the electrolyte contains PS, and the mass percentage of PS in the electrolyte is 5%.
[0129] Example 2 to Example 32, Comparative Examples 1 to 2: The difference from Example 1 is that the average maximum particle size D1 of the silicon carbon particles, the graphite particle size D2 in the bottom layer (first coating), the graphite particle size D3 in the upper layer (second coating), D1 / D2, D3 / D2, the average particle size D1 of the ceramic material, 31 、D3 / D 31 , the thickness of the ceramic layer H 31 , the mass percentage of sulfonic acid ester in the electrolyte e, the tensile strength of carbon-coated copper foil S1, S1 / e, the silicon doping amount of the negative electrode active layer X, the thickness of the carbon-coated copper foil H 10 , H 10×S1 / X, yttrium doping amount y, y / X, aluminum foil thickness H 20 , Tensile strength of aluminum foil S2, H 20 ×S2 / X, or the silicon content a in silicon carbon, a×X and other conditions are different, see Table 1 and Table 2 for details. Except for the differences shown in Table 1 and Table 2, other conditions are the same.
[0130] Example 30: The difference from Example 1 is that the ceramic layer of the diaphragm is located on the side of the base membrane facing the positive electrode sheet, and no ceramic layer is provided on the side of the base membrane facing the positive electrode sheet. The other conditions are the same as those in Example 1.
[0131] The negative electrode sheets and batteries of the embodiments and comparative examples were tested by the following methods:
[0132] (1) The battery capacity test method is: in a 25°C constant temperature room, use 0.2C constant current and constant voltage to charge to the upper limit voltage of the battery cell, then charge at a constant voltage with a cut-off current of 0.02C. After standing for 10 minutes, discharge at 0.2C to 3.0V. The measured battery capacity is shown in Table 3.
[0133] (2) Expansion rate of the battery after 500 cycles: In a 45°C constant temperature room, charge at 4C constant current to 4.25V, then charge at 3C constant current to 4.35V, then charge at 2C constant current to the upper limit voltage, charge at constant voltage to the cut-off current of 0.05C, let stand for 10 minutes, and then discharge at 1C to 3.0V. After 500 cycles, the battery cycle expansion rate is shown in Table 3;
[0134] (3) Electrode fracture rate: at 45°C, constant current and voltage of 1C to the upper limit voltage, cut off at 0.05C, let stand for 10 min, then discharge at 0.5C to 3.0V. After 600T of cycles, disassemble the battery to observe whether the positive electrode is broken. A total of 100 batteries were tested according to this process, and the electrode fracture rate (the proportion of batteries with broken positive electrodes to 100 batteries) was calculated. The results are shown in Table 3.
[0135] (4) Yttrium doping amount y in the positive electrode active layer: After the battery is discharged to 0% SOC, the positive electrode plate is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate. The positive electrode powder is calcined in an air atmosphere at 400°C in a high-temperature furnace for 2 hours, and the positive electrode powder is rubbed off. The concentration of aluminum in the standard solution is measured by inductively coupled plasma (ICP) according to the test method in GBT 30902-2014, which is the yttrium doping amount y in the positive electrode active layer, in ppm;
[0136] (5) Tensile strength of carbon-coated copper foil in battery: After the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the negative electrode sheet. The negative electrode active layer is then rinsed off from the negative electrode sheet with deionized water to obtain a complete copper foil. After drying, the copper foil is cut into test samples with a width of 15 mm and a length of more than 50 mm using a cutter; a WD-D3 electronic universal testing machine (with a precision of 0.5 level and an accuracy of ±1% of the indicated value) is used to set the gauge length to 50 mm and the speed to 50 mm / min, and a tensile test is performed on the test sample to measure the tensile strength;
[0137] (6) Tensile strength of aluminum foil in battery: After the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 h and then rinsed with DMC to remove the lithium salt attached to the positive electrode sheet. The empty foil at the end of the coil core is taken or the positive electrode active layer is wiped with CMC using a dust-free wiper to obtain a complete and intact aluminum foil. After drying, the aluminum foil is cut into test samples with a width of 15 mm and a length of more than 50 mm using a cutter. A WD-D3 electronic universal testing machine (with a precision of 0.5 level and an accuracy of ±1% of the indicated value) is used to set the gauge length to 50 mm and the speed to 10 mm / min. The test sample is subjected to a tensile test to measure the tensile strength of the aluminum foil.
[0138] Table 1 Battery related parameters
[0139]
[0140]
[0141] Table 2 Battery related parameters
[0142]
[0143]
[0144] Table 3 Performance test results
[0145] Example Pole fracture rate Cycle expansion rate capacity Example 1 0% 9% 4980 Example 2 9% 14% 5000 Example 3 0% 9% 4950 Example 4 12% 11% 4900 Example 5 0% 9% 4990 Example 6 0% 12% 4990 Example 7 8% 11% 4980 Example 8 0% 9% 4990 Example 9 1% 10% 4990 Example 10 35% 9% 4980 Embodiment 11 0% 9% 4980 Example 12 0% 9% 4980 Embodiment 13 0% 12% 4980 Embodiment 14 25% 9% 5200 Embodiment 15 0% 9% 5200 Example 16 0% 9% 4900 Embodiment 17 0% 9% 4900 Embodiment 18 0% 9% 4900 Embodiment 19 0% 9% 4900 Embodiment 20 0% 9% 5200 Embodiment 21 0% 14% 5200 Embodiment 22 38% 9% 5200 Embodiment 23 0% 9% 4900 Embodiment 24 0% 9% 4800 Embodiment 25 10% 9% 5200 Embodiment 26 0% 9% 4980 Embodiment 27 0% 9% 4980 Embodiment 28 5% 9% 5200 Embodiment 29 0% 17% 4980 Embodiment 30 16% 11% 4980 Embodiment 31 0% 10.5% 4965 Embodiment 32 0% 8.5% 4970 Comparative Example 1 45% 11% 4990 Comparative Example 2 100% 15% 4970
[0146] It can be seen from Table 1, Table 2 and Table 3 that, compared with Comparative Examples 1 to 2, Examples 1 to 32 are implemented by synergistically regulating the average particle size D3 of the graphite in the second coating layer, the thickness H of the ceramic layer, 31 , the average particle size D of ceramic materials 31 , so that it satisfies 5≤D3 / D 31≤350, which can effectively inhibit the fracture of the pole piece, and take into account the reduction of the battery cycle expansion rate, while taking into account the improvement of the battery capacity, especially embodiment 1, embodiment 3, embodiment 5, embodiment 6, embodiment 8, embodiment 9, embodiment 12, embodiment 16, embodiment 19, embodiment 23, embodiment 26, embodiment 28 can relatively more significantly reduce the pole piece fracture rate (no more than 5%, most of which are 0%), reduce the battery cycle expansion rate (no more than 12%), while taking into account the maintenance of a higher battery capacity, which further illustrates that when 4≤D3 / D is satisfied 31 ≤70、0.5≤D1 / D2≤1.5、0.3≤D3 / D2≤1、S1≥400MPa、550≤S1 / e≤60000、1600≤H 10 ×S1 / X≤660000, 100ppm≤y≤2000ppm, 400≤y / X≤200000, 600≤H 20 When at least one of the following conditions is met: ×S2 / X≤300000, 0.35%≤a×X≤35%, 35%≤a≤70%, it is possible to further reduce the risk of electrode breakage and inhibit battery expansion while maintaining high battery capacity and other performance.
[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery, characterized in that: include: A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a second coating layer and a first coating layer located between the negative electrode current collector and the second coating layer, wherein the first coating layer comprises a first active material, wherein the first active material comprises a silicon-carbon material, and the second coating layer comprises a second active material, wherein the second active material comprises a second graphite; A diaphragm, comprising a base film and a ceramic layer located on at least one side surface of the base film, wherein the ceramic layer comprises a ceramic material; The average particle size D3 of the second graphite in the second coating layer and the average particle size D 31 Satisfies: 3≤D3 / D 31 ≤350; The thickness H of the ceramic layer 31 Satisfy 0.5μm≤H 31 ≤6μm.
2. The battery according to claim 1, characterized in that 4≤D3 / D 31 ≤70; and / or, 5 μm ≤ D3 ≤ 22 μm; and / or, 50nm≤D 31 ≤2μm; and / or, the first active material further comprises a first graphite; Preferably, the average particle size D2 of the first graphite in the first coating is greater than the average particle size D3 of the second graphite in the second coating, preferably 0.3≤D3 / D2≤1; Preferably, the maximum particle size D1 of the silicon-carbon material in the first coating layer and the average particle size D2 of the first graphite in the first coating layer satisfy 0.5≤D1 / D2≤1.5; Preferably, 5 μm ≤ D1 ≤ 20 μm.
3. The battery according to claim 1, characterized in that The battery also includes an electrolyte, the electrolyte including a sulfonate; Preferably, the mass percentage content e of the sulfonic acid ester in the electrolyte and the tensile strength S1 of the negative electrode current collector satisfy S1 / e≥550, preferably 550≤S1 / e≤60000, and the unit of S1 is MPa; Preferably, the tensile strength S1 of the negative electrode current collector is ≥400MPa; Preferably, the mass percentage e of the sulfonic acid ester in the electrolyte is 0.1% to 20%; Preferably, the sulfonate ester comprises 1,3-propane sultone and / or 1,3-propene sultone.
4. The battery according to claim 1, characterized in that The thickness H of the negative electrode current collector 10 , the tensile strength S1 of the negative electrode current collector, the mass ratio X of the silicon-carbon material to the graphite in the negative electrode active layer satisfies H 10 ×S1 / X≥1600, preferably 1600≤(H 10 ×S1) / X≤660000, S1 is in MPa, H 10 The unit is μm; Preferably, 3 μm ≤ H 10 ≤12μm; Preferably 1%≤X≤50%.
5. The battery according to claim 1, characterized in that The ceramic layer is located on a surface of the base film facing the negative electrode sheet; And / or, the battery further comprises a positive electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet; and the bonding force between the separator and the positive electrode sheet is greater than the bonding force between the separator and the negative electrode sheet.
6. The battery according to claim 1, characterized in that The battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material contains yttrium element; Preferably, the first coating layer further comprises graphite, 400≤y / X≤200000, y is the yttrium content in the positive electrode active layer, the unit of y is ppm, and X is the mass ratio of the silicon-carbon material to the graphite in the negative electrode active layer; Preferably, 100 ppm≤y≤2000 ppm.
7. The battery according to claim 1, characterized in that The battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side surface of the positive electrode current collector; H 20 ×S2 / X≥600, preferably 600≤(H 20 ×S2) / X≤300000,H 20 is the thickness of the positive electrode current collector, in μm, S2 is the tensile strength of the positive electrode current collector, in MPa, and X is the mass ratio of the silicon-carbon material to the graphite in the negative electrode active layer; Preferably, 5 μm ≤ H 20 ≤20μm; Preferably, 50Mpa≤S2≤300Mpa.
8. The battery according to claim 1, characterized in that The first coating also includes a first graphite; And / or, the mass ratio X of the silicon-carbon to the graphite in the negative electrode active layer and the mass percentage a of the silicon element in the silicon-carbon material satisfy 0.35%≤a×X≤35%; And / or, the mass percentage a of silicon element in the silicon-carbon material is 35% to 70%; And / or, the silicon content in the silicon-carbon material shows a decreasing trend from the center of the silicon-carbon particle to the edge of the silicon-carbon particle; And / or, the mass ratio of the silicon carbon to the graphite in the negative electrode active layer is 1% to 50%, preferably 4% to 30%.
9. The battery according to any one of claims 1 to 8, characterized in that: The surface of the second coating layer is provided with a concave portion; Preferably, the width of the concave portion is 50 μm to 160 μm; Preferably, the depth of the concave portion is 3 μm to 40 μm; Preferably, the interval between the recesses is 0.3-3 mm.
10. The battery according to any one of claims 1 to 8, characterized in that The negative electrode sheet includes a negative electrode tab; The negative electrode active layer comprises a main body region, a first recessed region, and a second recessed region located between the main body region and the first recessed region, and the negative electrode tab is arranged in the first recessed region; The battery also includes tab tape, which includes a first connecting portion located on the side of the negative electrode tab away from the negative electrode collector, and a second connecting portion located on the side of the first recessed area away from the negative electrode collector, and a surface of the second connecting portion facing away from the negative electrode collector does not exceed a surface of the main area facing away from the negative electrode collector.
Citation Information
Patent Citations
Silicon-based negative lithium-ion battery and manufacturing method thereof
CN102694200A
Silicon-containing negative plate and lithium ion battery
CN117855383A
Negative plate and battery
CN118335903A
Negative electrode for nonaqueous electrolyte secondary battery, method for producing same, and nonaqueous electrolyte secondary battery
WO2012001840A1
Cited By
Negative plate, lithium ion battery and electric device
CN120565564A